Preoperative cholangitis is associated with increased surgical site infection following pancreaticoduodenectomy. (2nd July 2020) - Akashi, Masanori; Nagakawa, Yuichi; Hosokawa, Yuichi; Takishita, Chie; Osakabe, Hiroaki; Nishino, Hitoe; Katsumata, Kenji; Akagi, Yoshito; Itoi, Takao; Tsuchida, Akihiko
Abstract: Background: Few reports describe the relationship between preoperative cholangitis and surgical site infections (SSIs) after pancreaticoduodenectomy (PD). We aimed to determine the association between the incidence of preoperative cholangitis and surgical site infection following PD. Methods: The surgical outcomes of 359 patients who underwent PD were compared between patients with (n = 92) and without (n = 267) preoperative cholangitis. Bacterial cultures from the postoperative drainage fluid were examined. Risk factors for postoperative infectious complication were evaluated. Results: The incidence of postoperative infectious complications including grade B/C postoperative pancreatic fistula was high among patients with preoperative cholangitis ( P < .01). The positive rate of bacterial culture in the drainage fluid until postoperative day 3 ( P < .01) and the detection rate of Enterococcus species ( P < .01) were higher in the preoperative cholangitis group. The most common cause of preoperative cholangitis was drainage device dysfunction mainly with plastic stent occlusion. In the multivariate analysis, preoperative cholangitis (odds ratio 2.04, 95% confidence interval 1.13 to 3.69; P = .02) was an independent risk factor for postoperative infectious complications. Conclusions: Preoperative cholangitis significantly increased ascitic bacterial contamination and the incidence of postoperative infectious complications. after PD. Appropriate preoperative biliary drainage for the prevention of preoperative cholangitis is important for improving outcomes after PD. Abstract : Highlight Akashi and colleagues retrospectively analyzed data from 359 patients and investigated the impact of preoperative cholangitis on the occurrence of surgical site infection after pancreaticoduodenectomy. They concluded that preoperative cholangitis caused ascitic bacterial contamination in the early postoperative period and was an independent risk factor for the postoperative infectious complication.